Lithium transition metal oxide, positive electrode additive for lithium secondary battery, and lithium secondary battery containing the same

By using lithium cobalt oxide doped with heterogeneous elements as the positive electrode material of lithium secondary batteries, the reduction in capacity and irreversible reactions caused by volume changes during charging and discharging of lithium secondary batteries is solved, and the effect of reducing gas generation and improving battery safety and life is achieved.

CN115119528BActive Publication Date: 2025-04-04LG CHEM LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180012566.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-12
Filing Date
2021-08-17
Publication Date
2025-04-04
Estimated Expiration
2041-08-17

AI Technical Summary

Technical Problem

During the charging and discharging process, the capacity of existing lithium secondary batteries decreases due to the volume changes of metal and metal oxide negative electrode materials, and irreversible reactions occur in the chemical formation process, resulting in lithium loss and gas generation, affecting the safety and life of the battery.

Method used

Lithium cobalt oxide containing heterogeneous elements is used as the positive electrode material, and prepared by solid phase mixing and calcining, and the particle size distribution and heterogeneous elements content are controlled to inhibit side reactions with the electrolyte.

Benefits of technology

It effectively reduces the gas production in the positive electrode of the lithium secondary battery, improves the safety and life of the battery, and maintains excellent battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115119528B_ABST
    Figure CN115119528B_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium transition metal oxide, a positive electrode additive for a lithium secondary battery, and a lithium secondary battery containing the same. According to the present invention, a lithium transition metal oxide is provided, which can minimize side reactions with an electrolyte, thereby suppressing gas generation during charging and discharging of a lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2021-0009337 filed on January 22, 2021, Korean Patent Application No. 10-2021-0106774 filed on August 12, 2021, Korean Patent Application No. 10-2021-0106775 filed on August 12, 2021, and Korean Patent Application No. 10-2021-0106776 filed on August 12, 2021, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein in their entirety by reference.

[0003] The present invention relates to a lithium transition metal oxide, a positive electrode additive for a lithium secondary battery and a lithium secondary battery containing the same. Background Art

[0004] As power consumption increases with the multifunctionalization of electronic devices, many attempts have been made to increase the capacity of lithium secondary batteries and improve the charge / discharge efficiency thereof.

[0005] As an example, a technology is proposed in which a positive electrode active material having at least 80% Ni is applied to the positive electrode of a lithium secondary battery as a positive electrode material, and a metal or metal-based negative electrode active material such as SiO, Si or SiC is applied to the negative electrode together with a carbon-based negative electrode active material such as natural graphite, artificial graphite, etc.

[0006] Metal and metal oxide negative electrode active materials are able to achieve higher capacity than carbon negative electrode active materials. However, in the case of metal and metal oxide negative electrode active materials, the volume change during charging and discharging is much greater than that in the case of graphite, making it difficult to increase the content of metal and metal oxide in the negative electrode to more than 15%. In addition, when metals and metal oxides are added to the negative electrode, irreversible reactions occur during initial charging and discharging, whereby the loss of lithium is greater than when carbon negative electrode active materials are used. Therefore, when metal and metal oxide negative electrode active materials are applied, the amount of lithium loss increases as the battery capacity increases, whereby the degree of reduction in initial capacity also increases.

[0007] Therefore, various methods of increasing the capacity of lithium secondary batteries or reducing irreversible capacity have been studied. One of the methods is pre-lithiation, which is a concept of replenishing lithium consumed in forming a solid electrolyte interface (SEI) layer in the initial state of the battery.

[0008] Various methods have been proposed for pre-lithiation in batteries.

[0009] As an example, there is a method of electrochemically lithiating the negative electrode before driving the battery. However, the lithiated negative electrode is very unstable in the atmosphere, and the electrochemical lithiation method is difficult to scale up the process.

[0010] As another example, there is a method using lithium metal or lithium silicide (Li x Si) A method of coating a negative electrode with a powder. However, the powder has low atmospheric stability due to its high reactivity, which makes it difficult to establish a suitable solvent and process conditions when coating the negative electrode.

[0011] As a pre-lithiation method in the positive electrode, there is a method of coating with the same amount of positive electrode material as the amount of lithium consumed by the negative electrode. However, because the capacity of the positive electrode material itself is low, the amount of positive electrode material added increases, and the energy density and capacity per unit weight of the final battery decrease as much as the amount of positive electrode material added.

[0012] Therefore, materials suitable for battery pre-lithiation in the positive electrode need to have irreversible properties, in which the lithium desorbed during the initial charge of the battery is at least twice that of conventional positive electrode materials, and the material does not react with lithium during the subsequent discharge process. Additives that meet the above conditions are called sacrificial positive electrode materials.

[0013] Commercial batteries undergo a formation process in which an electrolyte is injected into a case containing a stacked positive electrode, a separator, and a negative electrode, and then the first charge / discharge operation is performed. In this process, a formation reaction of the SEI layer occurs on the negative electrode, and gas is generated due to the decomposition of the electrolyte. In the formation process, the sacrificial positive electrode material reacts with the electrolyte while releasing lithium and decomposing, and the gases such as N generated in the process are 2 , O 2 , CO 2 The gases are recovered through the air bag removal process.

[0014] As sacrificial positive electrode materials, lithium-rich metal oxides are widely used as over-lithiated positive electrode materials. As over-lithiated positive electrode materials, Li with an inverse fluorite structure is well known. 6 CoO 4 , Li 5 FeO 4 , Li 6 MnO 4 In terms of theoretical capacity, Li 6 CoO 4 977mAh / g, Li 5 FeO 4 is 867mAh / g, and Li 6 MnO 4 is 1001mAh / g, which is sufficient to be used as a sacrificial positive electrode material.6 CoO 4 It has the most excellent electrical conductivity and thus has good electrochemical performance as a sacrificial positive electrode material.

[0015] In the chemical process, Li 6 CoO 4 The process is gradually desorbed and decomposed, and the crystal phase collapses, which inevitably produces O 2 gas. Ideally, Li 6 CoO 4 No additional gas should be generated during the charge / discharge cycle after the formation process. If gas is continuously generated during the charge and discharge process, the pressure inside the battery increases, whereby the distance between the electrodes increases and the capacity and energy density of the battery decreases. In severe cases, the battery cannot withstand the pressure and may cause an explosion accident.

[0016] Therefore, it is necessary to develop a method that can make Li 6 CoO 4 The final crystalline phase of the electrochemical device is deactivated or stabilized to be inactive electrochemically so as not to generate additional gas during the charge / discharge cycle.

[0017] Prior art literature

[0018] (Patent Document 1) Korean Patent Publication No. 10-2013-0079109 (2013.07.10)

[0019] (Patent Document 2) Korean Patent Publication No. 10-2020-0066048 (2020.06.09) Summary of the invention

[0020] Technical issues

[0021] The present invention provides a lithium transition metal oxide, which can inhibit side reactions with electrolytes, thereby reducing gas generation in a positive electrode of a lithium secondary battery.

[0022] In the present invention, a method for preparing the lithium transition metal oxide is provided.

[0023] In the present invention, a positive electrode additive for a lithium secondary battery is provided, wherein the positive electrode additive comprises the lithium transition metal oxide.

[0024] In the present invention, a positive electrode for a lithium secondary battery is provided, the positive electrode comprising the lithium transition metal oxide.

[0025] In the present invention, a positive electrode for a lithium secondary battery is provided, wherein the positive electrode comprises the positive electrode additive for a lithium secondary battery.

[0026] In the present invention, a lithium secondary battery is provided. The lithium secondary battery includes the positive electrode for a lithium secondary battery.

[0027] Technical Solution

[0028] According to one embodiment of the present invention, a lithium transition metal oxide is provided, wherein the lithium transition metal oxide is a lithium cobalt oxide containing heteroelements.

[0029] wherein the heteroelement comprises: a 4th period transition metal; and at least one selected from a 2nd group element, a 13th group element, a 14th group element, a 5th period transition metal, and a 6th period transition metal, and

[0030] When the particle size distribution is measured by laser diffraction scattering, the cumulative 50% particle diameter (D50) is 10.0 μm to 25.0 μm, and the maximum particle diameter (D max ) and minimum particle size (D min ) ratio (D max / D min ) is 10.0 to 60.0.

[0031] According to another embodiment of the present invention, there is provided a method for preparing a lithium transition metal oxide, the method comprising:

[0032] The first step is to mix lithium oxide, cobalt oxide and heteroelement oxide in a solid phase; and

[0033] The second step is to obtain the lithium transition metal oxide by calcining the mixture obtained in the first step at a temperature of 550° C. to 750° C. under an inert atmosphere.

[0034] According to another embodiment of the present invention, a positive electrode additive for a lithium secondary battery is provided, the positive electrode additive comprising the lithium transition metal oxide.

[0035] According to another embodiment of the present invention, there is provided a positive electrode for a lithium secondary battery, the positive electrode including a positive electrode active material, a binder, a conductive material and the lithium transition metal oxide.

[0036] According to another embodiment of the present invention, there is provided a positive electrode for a lithium secondary battery, the positive electrode including a positive electrode active material, a binder, a conductive material, and the positive electrode additive for a lithium secondary battery.

[0037] According to another embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.

[0038] Hereinafter, the lithium transition metal oxide, the method of preparing the lithium transition metal oxide, the positive electrode additive for a lithium secondary battery, the positive electrode for a lithium secondary battery, and the lithium secondary battery according to an embodiment of the present invention will be described in more detail.

[0039] The terms or words used in the present invention and claims should not be construed as being limited to their ordinary or dictionary meanings, but should be construed as meanings and concepts consistent with the technical concept of the present invention on the basis of the principle that inventors can appropriately define the concepts of the terms to best describe their own inventions.

[0040] Unless otherwise defined in the present invention, all technical and scientific terms have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used in the description of the present invention are intended to be used only for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0041] The singular expression of the present invention may include the plural expression unless they are expressed differently in the context.

[0042] The terms "include", "comprising", etc. in the present invention are used to specify specific features, regions, integers, steps, operations, elements and / or components, and these do not exclude the existence or addition of other specific features, regions, integers, steps, operations, elements, components and / or groups.

[0043] Because the present invention can be variously modified and has multiple forms, its specific embodiment is shown by way of example and will be described in detail. However, this does not mean that the present invention is limited to the specific form disclosed, and it should be understood that the present invention includes all variants, equivalents and substitutions within the concept and technical scope of the present invention.

[0044] In the present invention, when the positional relationship of two parts is described as, for example, "on ~", "on the upper part of ~", "on the lower part of ~", "beside ~", etc., one or more other parts may be placed between the two parts, unless the expression "immediately" or "directly" is used.

[0045] In the present invention, when a time relationship is described as, for example, "after", "next", "subsequently", "before", etc., unless the expression "immediately" or "directly" is used, the case where events are discontinuous may be included.

[0046] In the present invention, it should be understood that the term "at least one" includes all possible combinations from one or more related items.

[0047] As used herein, the term "positive electrode additive" may refer to a material having an irreversible property, wherein the amount of lithium desorbed during the initial charge of the battery is at least twice that of a conventional positive electrode material and the material does not react with lithium during the subsequent discharge process. The positive electrode additive may be referred to as a sacrificial positive electrode material. Because the positive electrode additive compensates for the loss of lithium, the capacity of the battery may be increased by restoring the lost capacity of the battery, and gas generation may be suppressed to prevent battery explosion, thereby improving the life and safety of the battery.

[0048] As used herein, the term “stabilization of the crystalline phase” may refer to suppressing the formation of amorphous CoO after the initial charge of a lithium secondary battery. 2 The lithium secondary battery comprises a lithium cobalt oxide-based positive electrode additive into which a heteroelement is introduced. By suppressing the oxidation property of the amorphous CoO 2 The oxidizing properties of CoO 2 The side reaction between the electrolyte and the electrolyte can suppress gas generation.

[0049] I. Lithium Transition Metal Oxides

[0050] According to one embodiment of the present invention, a lithium transition metal oxide is provided, wherein the lithium transition metal oxide is a lithium cobalt oxide containing heteroelements.

[0051] wherein the heteroelement comprises: a 4th period transition metal; and at least one selected from a 2nd group element, a 13th group element, a 14th group element, a 5th period transition metal, and a 6th period transition metal, and

[0052] When the particle size distribution is measured by laser diffraction scattering, the cumulative 50% particle diameter (D50) is 10.0 μm to 25.0 μm, and the maximum particle diameter (D max ) and minimum particle size (D min ) ratio (D max / D min ) is 10.0 to 60.0.

[0053] As a result of the continuous research of the inventors, it has been confirmed that the lithium transition metal oxide that satisfies the above composition and particle size distribution minimizes the side reaction with the electrolyte, thereby suppressing the gas generation at the positive electrode during the charging and discharging of the lithium secondary battery while ensuring excellent battery performance. This may be because, by introducing the heteroelement of the above composition into the lithium transition metal oxide and satisfying the particle size distribution, a more stable crystalline phase is maintained and the reduction of the initial charge capacity is minimized. Therefore, the lithium transition metal oxide can improve the safety and life of the lithium secondary battery.

[0054] Since the lithium transition metal oxide contains two or more hetero elements satisfying the above composition, it is not suitable for lithium transition metal oxides such as Li6 CoO 4 In the present invention, the stabilization of the crystal phase refers to the suppression of the amorphous CoO formed after the initial charge of the lithium secondary battery containing the lithium cobalt oxide. 2 oxidizing properties.

[0055] At this point, when the 6 CoO 4 When the crystal phase of the electrode is checked by X-ray diffraction (XRD) after the lithium secondary battery is fully charged, the amorphous pattern is often not found. 6 CoO 4 In the case of Co 2+ The cation is first oxidized to Co 4+ cation, then O 2- The anions are oxidized to generate gas. When charging is completed, CoO without crystallinity is obtained. 2 (Co 4+ ) composition, thus no pattern was observed.

[0056] Co 4+ The cation has a high oxidizing property, which is Co 4+ The cation is either reduced to Co as is or during discharge (reduction reaction) 2+ Cation or Co 3+ The tendency of the cations to react with the surrounding electrolyte may result in side reactions, such as oxidation. Electrolytes such as carbonates decompose due to side reactions, producing CO 2 , CO and H 2 When the charge / discharge cycle is performed, the Co 2+ Cation or Co 3+ The cation is oxidized to Co 4+ Cation and Co 4+ The cations are reduced back to Co during discharge 2+ Cation or Co 3+ Cations cause gas to be continuously produced due to side reactions.

[0057] In order to suppress the side reactions, it is necessary to suppress the oxidation properties, that is, Co 4+ There is a tendency for the cation to be reduced. For example, there is a tendency for the Co to be stabilized by introducing heteroelements. 4+ The oxidation number of the cation.

[0058] In lithium transition metal oxides, by introducing heteroelements that can have a fixed oxidation number during charge and discharge of the battery, it is expected that Co 4+The average oxidation number of the cations can be reduced. 4+ The oxidizing properties of the cations can also suppress gas generation caused by side reactions.

[0059] However, as the amount of heteroelement with a fixed oxidation number introduced during the charge and discharge process of the battery increases, the initial charge capacity may be relatively reduced and the conductivity may tend to decrease. Therefore, a 4th period transition metal may be introduced as a main element of the heteroelement together with a secondary element capable of supplementing the electrochemical properties of the main element, thereby exhibiting a stabilization effect of the crystal phase while ensuring excellent battery performance.

[0060] Lithium transition metal oxides have two or more heteroelements alloyed or doped into Li 6 CoO 4 The composition of .

[0061] In this article, "alloy" means that the heteroelement is introduced in an amount of 10 mol% or more based on all the metal elements except lithium in the lithium transition metal oxide. In addition, "doping" means that the heteroelement is introduced in an amount of less than 10 mol% based on all the metal elements except lithium in the lithium transition metal oxide.

[0062] The lithium transition metal compound contains a 4th period transition metal as a main element of a heteroelement.

[0063] Furthermore, the lithium transition metal compound contains, as a sub-element of the heteroelement, at least one element selected from the group consisting of Group 2 elements, Group 13 elements, Group 14 elements, Period 5 transition metals, and Period 6 transition metals.

[0064] Specifically, the 4th period transition metal includes at least one selected from the group consisting of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn.

[0065] In addition, the Group 2 elements include at least one selected from the following: Mg, Ca, Sr and Ba; the Group 13 elements include at least one selected from the following: Al, Ga and In; the Group 14 elements include at least one selected from the following: Si, Ge and Sn; the 5th period transition metals include at least one selected from the following: Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag and Cd; and the 6th period transition metals include at least one selected from the following: Lu, Hf, Ta, W, Re, Os, Ir, Pt and Au.

[0066] Preferably, in terms of ease of alloying or doping with lithium cobalt oxide and stabilization of the crystal phase, the lithium transition metal compound may contain the 4th period transition metal Zn as a main element of the heteroelement; and may include at least one element selected from the following as a secondary element: Al, Mg, Ti, Zr, Nb and W.

[0067] Zn, Al, Mg, Ti, Zr, Nb, and W can be used as Li 6 CoO 4 The Co sites in the antifluorite lattice structure of the crystal phase are well substituted, and the oxidation number itself can remain unchanged. For example, Zn can have Li 6 ZnO 4 crystalline phase and easily react with Li 6 CoO 4 The alloy is formed, and its oxidation number may not change from 2+, thereby effectively suppressing the Co 4+ Oxidizing properties of cations.

[0068] The hetero element may be selected in consideration of whether M can exist in the inverse fluorite lattice structure of lithium cobalt oxide and whether M has a fixed oxidation number during charge and discharge of the battery.

[0069] For example, among the 4th period transition metals, Zn has Li 6 ZnO 4 crystalline phase, and can easily react with Li 6 CoO 4 In addition, the oxidation number does not change at 2+, which can effectively suppress Co after the initial charge. 4+ Oxidizing properties of cations.

[0070] As another example, in the case where Li does not satisfy the composition 5 FeO 4 and Li 6 MnO 4 In the case of , an antifluorite lattice structure can be formed. However, Mn can have multiple oxidation numbers of 2+, 3+, 4+ and 7+, and Fe can have multiple oxidation numbers of 2+ and 3+. Therefore, when CoO, MnO, Fe 2 O 3 When mixed and calcined, Mn or Fe can be oxidized and Co 2+ The cation may be reduced to produce Co 0 , that is, Co metal, which does not have an antifluorite lattice structure with a single crystal phase. Even if an alloyed Li 6 CoO 4In the case of Mn or Fe, since the oxidation number easily changes within the operating voltage, it may also be difficult to suppress Co after the initial charge. 4+ Oxidizing properties of cations.

[0071] The hetero element may be contained in an amount of 5 mol % to 80 mol % based on all metal elements except lithium in the lithium transition metal oxide.

[0072] Preferably, the content of the heteroelement is 5 mol% or more based on all metal elements except lithium, so that the stabilization effect of the crystal phase can be exhibited. However, when an excessive amount of heteroelement is introduced, the conductivity of the lithium transition metal oxide may be reduced, thereby increasing the resistance of the electrode and causing the battery performance to deteriorate. Therefore, preferably, the content of the heteroelement is 80 mol% or less based on all metal elements except lithium.

[0073] Specifically, the content of the hetero element may be 5 mol % or more, 10 mol % or more, or 15 mol % or more; and 80 mol % or less, 70 mol % or less, or 60 mol % or less, based on all metal elements except lithium.

[0074] Preferably, the content of the hetero element may be 10 mol % to 80 mol %, 10 mol % to 70 mol %, 15 mol % to 70 mol %, or 15 mol % to 60 mol % based on all metal elements except lithium.

[0075] In addition, the content ratio of the main element (4th period transition metal) and the auxiliary element (at least one element selected from the following: Group 2 elements, Group 13 elements, Group 14 elements, 5th period transition metals and 6th period transition metals) can be determined within the content range of the heteroelement.

[0076] For example, the content of the period 4 transition metal in the hetero element may be 10 mol % to 70 mol % based on all metal elements except lithium in the lithium transition metal oxide.

[0077] Preferably, the content of the 4th period transition metal in the lithium transition metal oxide is 10 mol% or more based on all metal elements except lithium, so that the stabilization effect of the crystalline phase can be exhibited. However, when excessive heteroelements are introduced, the conductivity of the lithium transition metal oxide may be reduced, thereby increasing the resistance of the electrode and causing the battery performance to deteriorate. Thus, preferably, based on all metal elements except lithium, the content of the 4th period transition metal in the lithium transition metal oxide is 70 mol% or less.

[0078] Specifically, based on all metal elements except lithium, the content of the 4th period transition metal in the lithium transition metal oxide can be greater than 10 mol%, greater than 15 mol% or greater than 20 mol%; and less than 70 mol%, less than 50 mol% or less than 30 mol%.

[0079] Preferably, based on all metal elements except lithium, the content of the 4th period transition metal in the lithium transition metal oxide can be 10 mol% to 70 mol%, 15 mol% to 70 mol%, 15 mol% to 50 mol%, 20 mol% to 50 mol% or 20 mol% to 30 mol%.

[0080] The stabilization effect of the crystal phase of the lithium transition metal oxide can be expected to be proportional to the content of the heteroelement. However, as the amount of the introduced heteroelement such as electrochemically inert Zn increases, the initial charge capacity may be relatively reduced and the conductivity may tend to decrease.

[0081] Therefore, it is preferred that the content of the accessory element among the heteroelements is 1 mol % or more based on all the metal elements except lithium.

[0082] However, when excessive impurity elements are introduced, the conductivity of the lithium transition metal oxide may decrease, thereby increasing the resistance of the electrode and causing the battery performance to deteriorate. Therefore, it is preferred that the content of the accessory elements in the lithium transition metal oxide is 20 mol% or less based on all metal elements except lithium.

[0083] Specifically, based on all metal elements except lithium, the content of accessory elements in the lithium transition metal oxide can be 1 mol% or more, 2 mol% or more, or 3 mol% or more; and 20 mol% or less, 17 mol% or less, or 15 mol% or less.

[0084] Preferably, the content of the accessory elements in the lithium transition metal oxide may be 1 mol % to 20 mol %, 2 mol % to 20 mol %, 2 mol % to 17 mol %, 3 mol % to 17 mol % or 3 mol % to 15 mol % based on all metal elements except lithium.

[0085] The lithium transition metal oxide can be represented by the following chemical formula 1:

[0086] [Chemical formula 1]

[0087] Li 6 Co 1-x-y Zn x M y O 4

[0088] In Chemical Formula 1,

[0089] M is a Group 2 element, a Group 13 element, a Group 14 element, a Period 5 transition metal, or a Period 6 transition metal,

[0090] x is 0.1 to 0.7,

[0091] y is 0.01 to 0.2.

[0092] Preferably, M in Chemical Formula 1 may be at least one element selected from the group consisting of Al, Mg, Ti, Zr, Nb, and W.

[0093] In Chemical Formula 1, x is 0.1 to 0.7, and y is 0.01 to 0.2.

[0094] Specifically, x may be 0.1 or more, 0.15 or more, or 0.2 or more, and 0.7 or less, 0.5 or less, or 0.3 or less. Preferably, x may be 0.1 to 0.7, 0.15 to 0.7, 0.15 to 0.5, 0.2 to 0.5, or 0.2 to 0.3.

[0095] y may be 0.01 or more, 0.02 or more, or 0.03 or more, and 0.2 or less, 0.17 or less, or 0.15 or less. Preferably, y may be 0.01 to 0.2, 0.02 to 0.2, 0.02 to 0.17, 0.03 to 0.17, or 0.03 to 0.15.

[0096] In addition, in Chemical Formula 1, the value of x+y may be 0.05 or more, 0.10 or more, 0.15 or more, or 0.20 or more; and 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less.

[0097] That is, it is preferred that the value of x+y in Chemical Formula 1 is 0.05 or more, 0.10 or more, 0.15 or more, or 0.20 or more, so that the stabilization effect of the crystal phase of the lithium transition metal oxide can be exhibited. However, when the value of x+y is too large, the conductivity of the lithium transition metal oxide is reduced, thereby deteriorating the performance of the battery. Therefore, the value of x+y in Chemical Formula 1 is preferably 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less.

[0098] Specifically, in Chemical Formula 1, the value of x+y may be 0.05 to 0.80, 0.10 to 0.80, 0.15 to 0.80, 0.15 to 0.70, 0.15 to 0.60, 0.20 to 0.60, or 0.20 to 0.50.

[0099] Preferably, the lithium transition metal oxide may include at least one compound selected from the following: Li 6 Co 0.77 Zn 0.2 Al0.03 O 4 、Li 6 Co 0.76 Zn 0.2 Al 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 Al 0.05 O 4 、Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4 、Li 6 Co 0.65 Zn 0.25 Al 0.1 O 4 、Li 6 Co 0.67 Zn 0.3 Al 0.03 O 4 、Li 6 Co 0.66 Zn 0.3 Al 0.04 O 4 、Li 6 Co 0.65 Zn 0.3 Al 0.05 O 4 、Li 6 Co 0.6 Zn 0.3 Al 0.1 O 4 、Li 6 Co 0.77 Zn 0.2 Mg 0.03 O 4 、Li 6 Co 0.76 Zn 0.2 Mg 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 Mg 0.05 O 4 、Li 6 Co 0.7 Zn 0.25 Mg 0.05 O 4 、Li 6 Co 0.67 Zn 0.3 Mg 0.03 O 4,If 6 What 0.66 Zn 0.3 Mg 0.04 O 4 ,If 6 What 0.65 Zn 0.3 Mg 0.05 O 4 ,If 6 What 0.77 Zn 0.2 Those 0.03 O 4 ,If 6 What 0.76 Zn 0.2 Those 0.04 O 4 ,If 6 What 0.75 Zn 0.2 Those 0.05 O 4 ,If 6 What 0.72 Zn 0.25 Those 0.03 O 4 ,If 6 What 0.67 Zn 0.3 Those 0.03 O 4 ,If 6 What 0.66 Zn 0.3 Those 0.04 O 4 ,If 6 What 0.65 Zn 0.3 Those 0.05 O 4 ,If 6 What 0.77 Zn 0.2 Zr 0.03 O 4 ,If 6 What 0.76 Zn 0.2 Zr 0.04 O 4 ,If 6 What 0.75 Zn 0.2 Zr 0.05 O 4 ,If 6 What 0.72 Zn 0.25 Zr 0.03 O 4 ,If 6 What0.67 Zn 0.3 Zr 0.03 O 4 、Li 6 Co 0.66 Zn 0.3 Zr 0.04 O 4 、Li 6 Co 0.65 Zn 0.3 Zr 0.05 O 4 、Li 6 Co 0.77 Zn 0.2 No 0.03 O 4 、Li 6 Co 0.76 Zn 0.2 No 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 No 0.05 O 4 、Li 6 Co 0.67 Zn 0.3 No 0.03 O 4 、Li 6 Co 0.66 Zn 0.3 No 0.04 O 4 、Li 6 Co 0.65 Zn 0.3 No 0.05 O 4 、Li 6 Co 0.77 Zn 0.2 W 0.03 O 4 、Li 6 Co 0.76 Zn 0.2 W 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 W 0.05 O 4 、Li 6 Co 0.67 Zn 0.3 W 0.03 O 4 、Li 6 Co 0.66 Zn 0.3 W0.04 O 4 and Li 6 Co 0.65 Zn 0.3 W 0.05 O 4 .

[0100] On the other hand, when measured by laser diffraction scattering particle size distribution, the lithium transition metal oxide has a cumulative 50% particle size (D50) of 10.0 μm to 25.0 μm, and a maximum particle size (D max ) and minimum particle size (D min ) ratio (D max / D min )) is 10.0 to 60.0.

[0101] In addition, when measured by laser diffraction scattering particle size distribution, the lithium transition metal oxide has a cumulative 5% particle size (D5) of 3.0 μm to 10.0 μm, and a cumulative 95% particle size (D95) of 20.0 μm to 45.0 μm.

[0102] Laser diffraction scattering particle size distribution measurement is a method of obtaining a particle size distribution from a diffraction image obtained by dispersing a lithium transition metal oxide in a dispersion medium, irradiating it with a laser beam, and focusing the generated scattered light (forward scattered light). Laser diffraction scattering particle size distribution measurement is relatively simple and fast, and can obtain a particle size distribution with excellent accuracy.

[0103] Herein, the cumulative 50% particle size (D50) refers to a particle size when the cumulative percentage reaches 50% from the minimum particle size based on mass using a laser diffraction scattering particle size distribution analyzer.

[0104] The cumulative 50% particle size (D50) of the lithium transition metal oxide is 10.0 μm to 25.0 μm.

[0105] Preferably, the D50 value is 10.0 μm or more to prevent the side reaction with the electrolyte from being aggravated due to the excessive specific surface area. However, when the particle size is too large, it is difficult to evenly coat the positive electrode material containing the lithium transition metal oxide on the collector, thereby causing damage to the collector during the rolling process after drying. Therefore, the D50 value is preferably 25.0 μm or less.

[0106] Specifically, the D50 value of the lithium transition metal oxide may be 10.0 μm or more, 10.5 μm or more, 11.0 μm or more, or 11.5 μm or more; and 25.0 μm or less, 24.0 μm or less, 23.0 μm or less, or 22.0 μm or less.

[0107] Preferably, the lithium transition metal oxide may have a D50 value of 10.5 μm to 25.0 μm, 10.5 μm to 24.0 μm, 11.0 μm to 24.0 μm, 11.0 μm to 23.0 μm, 11.5 μm to 23.0 μm, or 11.5 μm to 22.0 μm.

[0108] In addition, the maximum particle size (D max ) and minimum particle size (D min ) ratio (D max / D min ) is 10.0 to 60.0.

[0109] Smaller D max / D min However, in order to minimize the loss of lithium transition metal oxide and maximize the yield in the process of pulverizing and classifying the particles, D max / D min The value is preferably 10.0 or more.

[0110] On the other hand, when the difference between the maximum particle size and the minimum particle size is too large, the capacity of the particles with a small particle size may be excessively expressed, which may cause a serious side reaction with the electrolyte. In addition, compared with small particles, particles with a large particle size have a smaller specific surface area, thereby expressing a relatively low capacity. As a result, the average characteristics of the lithium transition metal oxide particles cannot be determined, and it is difficult to apply them to batteries, which may not be preferable in terms of reproducibility. Therefore, D max / D min The value is preferably 60.0 or less.

[0111] Specifically, the D of lithium transition metal oxides max / D min The value may be 10.0 or more, 11.0 or more, 12.0 or more, 13.0 or more, 14.0 or more, or 15.0 or more; and 60.0 or less, 59.0 or less, 58.0 or less, or 57.0 or less.

[0112] Preferably, the D of the lithium transition metal oxide max / D min The values ​​may be from 11.0 to 60.0, 11.0 to 59.0, 12.0 to 59.0, 12.0 to 58.0, 13.0 to 58.0, 13.0 to 57.0, 14.0 to 57.0, or 15.0 to 57.0.

[0113] The maximum particle size of lithium transition metal oxides (D max ) is 30.0 μm to 90.0 μm, and the minimum particle size (D min ) is 1.0μm to 5.0μm.

[0114] Specifically, the D of lithium transition metal oxides max The value may be 30.0 μm or more, 32.0 μm or more, 34.0 μm or more, 36.0 μm or more, or 38.0 μm or more; and 90.0 μm or less, 89.5 μm or less, 89.0 μm or less, 88.5 μm or less, or 88.0 μm or less. Preferably, the D max The values ​​may be 32.0 μm to 90.0 μm, 32.0 μm to 89.5 μm, 34.0 μm to 89.5 μm, 34.0 μm to 89.0 μm, 36.0 μm to 89.0 μm, 36.0 μm to 88.5 μm, 38.0 μm to 88.5 μm, or 38.0 μm to 88.0 μm.

[0115] Furthermore, the D of lithium transition metal oxides min The value may be 1.0 μm or more, 1.1 μm or more, or 1.2 μm or more; and 5.0 μm or less, 4.5 μm or less, 4.0 μm or less, 3.5 μm or less, or 3.0 μm or less. Preferably, the D of the lithium transition metal oxide min The values ​​may be 1.0 μm to 4.5 μm, 1.1 μm to 4.5 μm, 1.1 μm to 4.0 μm, 1.1 μm to 3.5 μm, 1.2 μm to 3.5 μm, or 1.2 μm to 3.0 μm.

[0116] In addition, the cumulative 5% particle size (D5) of the lithium transition metal oxide is 3.0 μm to 10.0 μm, and the cumulative 95% particle size (D95) is 20.0 μm to 45.0 μm.

[0117] Specifically, the D5 value of the lithium transition metal oxide may be 3.0 μm or more, 3.5 μm or more, 4.0 μm or more, 4.5 μm or more, or 5.0 μm or more; and 10.0 μm or less, 9.9 μm or less, or 9.8 μm or less. Preferably, the D5 value of the lithium transition metal oxide may be 3.5 μm to 10.0 μm, 4.0 μm to 10.0 μm, 4.0 μm to 9.9 μm, 4.5 μm to 9.9 μm, 4.5 μm to 9.8 μm, or 5.0 μm to 9.8 μm.

[0118] In addition, the D95 value of the lithium transition metal oxide may be 20.0 μm or more, 20.5 μm or more, or 21.0 μm or more; and 45.0 μm or less, 44.0 μm or less, or 43.0 μm or less. Preferably, the D95 value of the lithium transition metal oxide may be 20.5 μm to 45.0 μm, 20.5 μm to 44.0 μm, 21.0 μm to 44.0 μm, or 21.0 μm to 43.0 μm.

[0119] As a non-limiting example, the lithium transition metal oxide may have a D of 30.0 μm to 70.0 μm. max value and D from 10.0 to 30.0 max / D min Value. Satisfy D max Value and D max / D min The lithium transition metal oxide having a certain value may be a compound in which M in Chemical Formula 1 is a Group 13 element, preferably Al.

[0120] Lithium transition metal oxides have the property of irreversibly releasing lithium during the charge and discharge process of lithium secondary batteries. In particular, lithium transition metal oxides can inhibit side reactions with electrolytes, thereby improving the safety and life of lithium secondary batteries.

[0121] II. Methods for preparing lithium transition metal oxides

[0122] According to another embodiment of the present invention, there is provided a method for preparing a lithium transition metal oxide, the method comprising:

[0123] The first step is to mix lithium oxide, cobalt oxide and heteroelement oxide in a solid phase; and

[0124] The second step is to obtain the lithium transition metal oxide by calcining the mixture obtained in the first step at a temperature of 550° C. to 750° C. under an inert atmosphere.

[0125] In the above-mentioned first step, a raw material mixture containing lithium oxide, cobalt oxide and heteroelement oxide is provided.

[0126] As lithium oxide, Li 2 O-containing lithium oxide without particular limitation.

[0127] In addition, as the cobalt oxide, an oxide containing cobalt such as CoO may be used without particular limitation.

[0128] Regarding the content of the hetero element, refer to the description provided in "I. Lithium transition metal oxide" above.

[0129] As heteroelement oxides, oxides of transition metals of the 4th period and oxides of at least one element selected from the group consisting of Group 2 elements, Group 13 elements, Group 14 elements, transition metals of the 5th period and transition metals of the 6th period can be used. As non-limiting examples, oxides containing heteroelement such as ZnO, MgO, Al 2 O 3 、TiO 2 、ZrO 2, Nb 2 O 5 and WO 3 The oxide of the hetero element is not particularly limited.

[0130] A raw material mixture is prepared by solid-phase mixing lithium oxide, cobalt oxide, and heteroelement oxide so as to satisfy the stoichiometric ratio described in the above-mentioned "I. Lithium transition metal oxide".

[0131] In the second step, the raw material mixture obtained in the first step is calcined at a temperature of 550° C. to 750° C. in an inert atmosphere to obtain a lithium transition metal oxide.

[0132] The second step can be performed using an inert gas such as Ar, N 2 , Ne and He formed in an inactive atmosphere.

[0133] In the second step, preferably, the mixture obtained in the first step is heated at a heating rate of 1.4° C. / min to 2.0° C. / min in an inert atmosphere to reach a calcination temperature.

[0134] When the heating rate is too slow, the seed crystal may be formed slowly and the crystal may continue to grow, whereby the grain may become too large. Thus, it is preferred that the heating rate is 1.4°C / min or more. However, when the heating rate is too fast, a large number of seed crystals are generated at a very high rate, and the growth time of the grain may be relatively short, whereby the crystallinity may be relatively low and the grain size may be relatively small. Thus, it is preferred that the heating rate is 2.0°C / min or less.

[0135] Specifically, the heating rate may be 1.40°C / min or more, 1.45°C / min or more, or 1.50°C / min or more; and 2.00°C / min or less, 1.95°C / min or less, or 1.90°C / min or less. Preferably, the heating rate may be 1.40°C / min to 2.00°C / min, 1.45°C / min to 2.00°C / min, 1.45°C / min to 1.95°C / min, 1.50°C / min to 1.95°C / min, or 1.50°C / min to 1.90°C / min.

[0136] Calcination may be performed at a temperature of 550°C to 750°C.

[0137] It is preferred that the calcination temperature is 550° C. or higher so that seed crystals can be generated at an appropriate rate. However, when the calcination temperature is too high, a sintering phenomenon in which the grown crystal grains agglomerate may occur. Thus, it is preferred that the calcination temperature is 750° C. or lower.

[0138] Specifically, the calcination temperature may be 550°C or more, 580°C or more, or 600°C or more, and 750°C or less, 720°C or less, or 700°C or less. Preferably, the calcination temperature may be 580°C to 750°C, 580°C to 720°C, 600°C to 720°C, or 600°C to 700°C.

[0139] Calcination can be carried out at the calcination temperature for 2 to 20 hours. The calcination time can be adjusted by considering the time required for introducing heteroelements into the lithium cobalt oxide in the form of alloys or doping to stabilize the crystal. Specifically, the calcination time can be more than 2 hours, more than 3 hours, or more than 4 hours; and less than 20 hours, less than 19 hours, or less than 18 hours. Preferably, the calcination time can be 3 to 20 hours, 3 to 19 hours, 4 to 19 hours, or 4 to 18 hours.

[0140] The lithium transition metal oxide obtained in the second step may have a cumulative 50% particle size (D50) of 10.0 to 25.0 μm and a maximum particle size (D50) of 10.0 to 60.0 μm when measured by laser diffraction scattering particle size distribution. max ) and minimum particle size (D min ) ratio (D max / D min ). If necessary, pulverization and classification steps may be performed so that the lithium transition metal oxide may have the above-mentioned D50 value within the above-mentioned range.

[0141] Optionally, a step of washing and drying the compound represented by Chemical Formula 1 obtained in the second step may be performed.

[0142] As a non-limiting example, the washing process can be performed by mixing the compound of Chemical Formula 1 and a washing liquid at a weight ratio of 1:2 to 1:10 and then stirring. Distilled water, ammonia water, etc. can be used as the washing liquid. Drying can be performed by heat treatment at a temperature of 100°C to 200°C or 100°C to 180°C for 1 to 10 hours.

[0143] III. Positive electrode additives for lithium secondary batteries

[0144] According to another embodiment of the present invention, there is provided a positive electrode additive for a lithium secondary battery, comprising the above-mentioned lithium transition metal oxide.

[0145] Lithium transition metal oxides can minimize side reactions with electrolytes, thereby suppressing gas generation at the positive electrode during charging and discharging of lithium secondary batteries. Thus, positive electrode additives for lithium secondary batteries containing lithium transition metal oxides can improve the safety and life of lithium secondary batteries.

[0146] The positive electrode additive for lithium secondary batteries containing lithium transition metal oxide has the property of irreversibly releasing lithium during the charge and discharge process of the lithium secondary battery. Therefore, the positive electrode additive for lithium secondary batteries is contained in the positive electrode for lithium secondary batteries and functions as a sacrificial positive electrode material for pre-lithiation.

[0147] Regarding the contents of lithium transition metal oxides, reference is made to the description provided in the above “I. Lithium transition metal oxides”.

[0148] Lithium transition metal oxides have 6 CoO 4 The composition of alloying or doping with two or more impurity elements.

[0149] The lithium transition metal compound contains a period 4 transition metal as a main element as a heteroelement.

[0150] Furthermore, the lithium transition metal compound includes, as a sub-element of the heteroelement, at least one element selected from the group consisting of Group 2 elements, Group 13 elements, Group 14 elements, Period 5 transition metals, and Period 6 transition metals.

[0151] Specifically, the 4th period transition metal includes at least one selected from the group consisting of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn.

[0152] In addition, the Group 2 elements include at least one selected from the following: Mg, Ca, Sr and Ba; the Group 13 elements include at least one selected from the following: Al, Ga and In; the Group 14 elements include at least one selected from the following: Si, Ge and Sn; the 5th period transition metals include at least one selected from the following: Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag and Cd; and the 6th period transition metals include at least one selected from the following: Lu, Hf, Ta, W, Re, Os, Ir, Pt and Au.

[0153] Preferably, in terms of ease of alloying or doping with lithium cobalt oxide and stabilization of the crystal phase, the lithium transition metal compound may contain the 4th period transition metal Zn as a main element of the heteroelement; and may include at least one element selected from the following as a secondary element: Al, Mg, Ti, Zr, Nb and W.

[0154] The hetero element may be contained in an amount of 5 mol % to 80 mol % based on all metal elements except lithium in the lithium transition metal oxide.

[0155] The content of the period 4 transition metal among the hetero elements may be 10 mol % to 70 mol % based on all metal elements except lithium in the lithium transition metal oxide.

[0156] The content of the heteroelement as at least one selected from Group 2 elements, Group 13 elements, Group 14 elements, Period 5 transition metals, and Period 6 transition metals may be 1 mol % to 20 mol % based on all metal elements except lithium in the lithium transition metal oxide.

[0157] The lithium transition metal oxide can be represented by the following chemical formula 1:

[0158] [Chemical formula 1]

[0159] Li 6 Co 1-x-y Zn x M y O 4

[0160] In Chemical Formula 1,

[0161] M is a Group 2 element, a Group 13 element, a Group 14 element, a Period 5 transition metal, or a Period 6 transition metal,

[0162] x is 0.1 to 0.7,

[0163] y is 0.01 to 0.2.

[0164] Preferably, M in Chemical Formula 1 may be at least one element selected from the group consisting of Al, Mg, Ti, Zr, Nb, and W.

[0165] Preferably, the lithium transition metal oxide may include at least one compound selected from the following: Li 6 Co 0.77 Zn 0.2 Al 0.03 O 4 , Li 6 Co 0.76 Zn 0.2 Al 0.04 O 4 , Li 6 Co 0.75 Zn 0.2 Al 0.05 O 4 , Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4 , Li 6 Co 0.65 Zn 0.25 Al 0.1 O 4 , Li 6 Co 0.67 Zn 0.3 Al 0.03O 4 、Li 6 Co 0.66 Zn 0.3 Al 0.04 O 4 、Li 6 Co 0.65 Zn 0.3 Al 0.05 O 4 、Li 6 Co 0.6 Zn 0.3 Al 0.1 O 4 、Li 6 Co 0.77 Zn 0.2 Mg 0.03 O 4 、Li 6 Co 0.76 Zn 0.2 Mg 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 Mg 0.05 O 4 、Li 6 Co 0.7 Zn 0.25 Mg 0.05 O 4 、Li 6 Co 0.67 Zn 0.3 Mg 0.03 O 4 、Li 6 Co 0.66 Zn 0.3 Mg 0.04 O 4 、Li 6 Co 0.65 Zn 0.3 Mg 0.05 O 4 、Li 6 Co 0.77 Zn 0.2 Tea 0.03 O 4 、Li 6 Co 0.76 Zn 0.2 Tea 0.04 O 4 、Li 6 Co 0.75 Zn 0.2 Tea 0.05 O 4 、Li6 What 0.72 Zn 0.25 Those 0.03 O 4 ,If 6 What 0.67 Zn 0.3 Those 0.03 O 4 ,If 6 What 0.66 Zn 0.3 Those 0.04 O 4 ,If 6 What 0.65 Zn 0.3 Those 0.05 O 4 ,If 6 What 0.77 Zn 0.2 Zr 0.03 O 4 ,If 6 What 0.76 Zn 0.2 Zr 0.04 O 4 ,If 6 What 0.75 Zn 0.2 Zr 0.05 O 4 ,If 6 What 0.72 Zn 0.25 Zr 0.03 O 4 ,If 6 What 0.67 Zn 0.3 Zr 0.03 O 4 ,If 6 What 0.66 Zn 0.3 Zr 0.04 O 4 ,If 6 What 0.65 Zn 0.3 Zr 0.05 O 4 ,If 6 What 0.77 Zn 0.2 Nb 0.03 O 4 ,If 6 What 0.76 Zn 0.2 Nb 0.04 O 4 ,If 6 What 0.75Zn 0.2 Nb 0.05 O 4 , Li 6 Co 0.67 Zn 0.3 Nb 0.03 O 4 , Li 6 Co 0.66 Zn 0.3 Nb 0.04 O 4 , Li 6 Co 0.65 Zn 0.3 Nb 0.05 O 4 , Li 6 Co 0.77 Zn 0.2 W 0.03 O 4 , Li 6 Co 0.76 Zn 0.2 W 0.04 O 4 , Li 6 Co 0.75 Zn 0.2 W 0.05 O 4 , Li 6 Co 0.67 Zn 0.3 W 0.03 O 4 , Li 6 Co 0.66 Zn 0.3 W 0.04 O 4 and Li 6 Co 0.65 Zn 0.3 W 0.05 O 4 .

[0166] When measured by laser diffraction scattering particle size distribution, the lithium transition metal oxide has a cumulative 50% particle size (D50) of 10.0 μm to 25.0 μm, and a maximum particle size (D max ) and minimum particle size (D min ) ratio (D max / D min ) is 10.0 to 60.0.

[0167] The lithium transition metal oxide has a maximum particle size (D ) of 30.0 μm to 90.0 μm when measured by laser diffraction scattering particle size distribution. max ) and a minimum particle size (D min).

[0168] Furthermore, when measured by laser diffraction scattering particle size distribution, the lithium transition metal oxide has a cumulative 5% particle size (D5) of 3.0 μm to 10.0 μm, and a cumulative 95% particle size (D95) of 20.0 μm to 45.0 μm.

[0169] IV. Positive electrode for lithium secondary battery

[0170] According to another embodiment of the present invention, a positive electrode for a lithium secondary battery is provided.

[0171] The positive electrode for a lithium secondary battery may include a positive electrode active material, a binder, a conductive material, and a lithium transition metal oxide.

[0172] In addition, the positive electrode for a lithium secondary battery may include a positive electrode active material, a binder, a conductive material, and a positive electrode additive for a lithium secondary battery.

[0173] The lithium transition metal oxide and the positive electrode additive for lithium secondary batteries have the property of irreversibly releasing lithium during the charging and discharging process of the lithium secondary battery. Thus, the lithium transition metal oxide and the positive electrode additive for lithium secondary batteries can be included in the positive electrode for lithium secondary batteries and can function as a sacrificial positive electrode material for pre-lithiation.

[0174] Preferably, the positive electrode for a lithium secondary battery comprises: a positive electrode material comprising a positive electrode active material, a conductive material, a sacrificial positive electrode material and a binder; and a current collector for supporting the positive electrode material.

[0175] Herein, the sacrificial positive electrode material is a lithium transition metal oxide or a positive electrode additive for a lithium secondary battery. For the content of the sacrificial positive electrode material, refer to the description provided in the above “I. Lithium transition metal oxide” and “III. Positive electrode additive for lithium secondary battery”.

[0176] In the case of a high-capacity battery, in order to increase the battery capacity, it is necessary to further increase the proportion of the negative electrode active material in the negative electrode, thereby also increasing the amount of lithium consumed in the SEI layer. Therefore, after calculating the amount of lithium consumed in the SEI layer of the negative electrode, the amount of sacrificial positive electrode material to be coated on the positive electrode can be reversely calculated to determine the design capacity of the battery.

[0177] According to one embodiment, the content of the sacrificial positive electrode material may be greater than 0 wt % and less than 15 wt % based on the total weight of the positive electrode material.

[0178] Preferably, the content of the sacrificial positive electrode material is greater than 0 wt % based on the total weight of the positive electrode material to compensate for irreversible lithium consumed in the formation of the SEI layer.

[0179] However, when an excessive amount of sacrificial positive electrode material is included, the content of the positive electrode active material showing reversible charge / discharge capacity is reduced, thereby reducing the capacity of the battery, and the residual lithium in the battery is plated on the negative electrode, thereby causing a short circuit in the battery or hindering safety. Thus, the content of the sacrificial positive electrode material is preferably 15 wt % or less based on the total weight of the positive electrode material.

[0180] Specifically, based on the total weight of the positive electrode material, the content of the sacrificial positive electrode material is greater than 0 weight %, more than 0.5 weight %, more than 1 weight %, more than 2 weight % or more than 3 weight %; and is less than 15 weight %, less than 12 weight % or less than 10 weight %.

[0181] Preferably, based on the total weight of the positive electrode material, the content of the sacrificial positive electrode material can be 0.5 wt % to 15 wt %, 1 wt % to 15 wt %, 1 wt % to 12 wt %, 2 wt % to 12 wt %, 2 wt % to 10 wt % or 3 wt % to 10 wt %.

[0182] As the positive electrode active material, compounds known to be applicable to lithium secondary batteries in the art to which the present invention pertains may be used without particular limitation.

[0183] As a non-limiting example, the positive electrode active material may include NCM (Li[Ni, Co, Mn]O 2 )、NCMA(Li[Ni,Co,Mn,Al]O 2 ), LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 2 、LiNi 1-d Co d O 2 、LiCo 1-d Mn d O 2 、LiNi 1-d Mn d O 2 (where 0≤d<1), Li(Ni a Co b Mn c ) 4 (0 <a<2,0<b<2,0<c<2,a+b+c=2)、LiMn 2-e Ni e O 4 、LiMn 2-e Co e O 4 (where 0 <e<2)、LiCoPO 4 、LiFePO4 As the positive electrode active material, one or a mixture of two or more of the above examples may be used.

[0184] According to one embodiment, the positive electrode active material may be included in an amount of 80 wt % to 95 wt % based on the total weight of the positive electrode material.

[0185] Specifically, the content of the positive electrode active material may be 80 wt % or more, 82 wt % or more, or 85 wt % or more; and 95 wt % or less, 93 wt % or less, or 90 wt % or less, based on the total weight of the positive electrode material.

[0186] Preferably, the content of the positive electrode active material may be 82 wt % to 95 wt %, 82 wt % to 93 wt %, 85 wt % to 93 wt %, or 85 wt % to 90 wt % based on the total weight of the positive electrode material.

[0187] The conductive material is used to impart conductivity to the electrode.

[0188] The conductive material may be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery. As non-limiting examples, the conductive material may include: carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon fiber, etc.; graphite such as natural graphite, artificial graphite, etc.; metal powder or metal fiber such as copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; conductive polymers such as polyphenylene derivatives, etc.; or the like. As the conductive material, one or a mixture of two or more of the above examples may be used.

[0189] The content of the conductive material can be adjusted within a range that does not cause a decrease in battery capacity while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material can be 1 wt % to 10 wt % or 1 wt % to 5 wt % based on the total weight of the positive electrode material.

[0190] The binder is used to adhere the positive electrode material to the current collector well.

[0191] As non-limiting examples, the binder may be polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc. As the binder, one or a mixture of two or more of the above examples may be used.

[0192] The content of the binder can be adjusted within a range that does not cause a decrease in battery capacity while exhibiting an appropriate level of adhesiveness. Preferably, the content of the binder may be 1 wt % to 10 wt % or 1 wt % to 5 wt % based on the total weight of the positive electrode material.

[0193] As the current collector, materials known in the art to which the present invention pertains and applicable to a positive electrode of a lithium secondary battery may be used without particular limitation.

[0194] As non-limiting examples, the current collector used herein may include: stainless steel; aluminum; nickel; titanium; calcined carbon; aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.; or the like.

[0195] Preferably, the current collector may have a thickness of 3 μm to 500 μm. In order to improve the adhesion of the positive electrode material, the current collector may have fine concavoconvexities formed on its surface. The current collector may have various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven fabric body, etc.

[0196] The positive electrode for a lithium secondary battery may be formed by stacking a positive electrode material including a positive electrode active material, a conductive material, a sacrificial positive electrode material, and a binder on a current collector.

[0197] V. Lithium secondary battery

[0198] According to another embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.

[0199] The lithium secondary battery may include a positive electrode including a lithium transition metal oxide or a positive electrode additive for a lithium secondary battery. Thus, the lithium secondary battery can suppress gas generation at the positive electrode during charging and discharging, and can exhibit improved safety and life. In addition, the lithium secondary battery can exhibit high discharge capacity, excellent output characteristics and capacity retention rate.

[0200] Accordingly, lithium secondary batteries can be used as a source of energy supply with improved performance and safety in the following fields: portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras; and transportation vehicles such as electric vehicles, electric motorcycles, and personal mobility devices.

[0201] The lithium secondary battery may include: an electrode assembly wound with a separator disposed between a positive electrode and a negative electrode; and a case in which the electrode assembly is embedded. In addition, the positive electrode, the negative electrode, and the separator may be impregnated with an electrolyte.

[0202] The lithium secondary battery may have various shapes such as a prismatic shape, a cylindrical shape, a pouch shape, and the like.

[0203] Regarding the content of the positive electrode, refer to the description provided in "IV. Positive Electrode for Lithium Secondary Battery" above.

[0204] The negative electrode may include: a negative electrode material including a negative electrode active material, a conductive material, and a binder; and a current collector for supporting the negative electrode material.

[0205] The negative electrode active material may include a material capable of reversibly inserting and extracting lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0206] Examples of the material capable of reversibly inserting and extracting lithium ions may include crystalline carbon, amorphous carbon, or a mixture thereof as a carbonaceous material. Specifically, the carbonaceous material may be natural graphite, artificial graphite, condensated graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, mesophase carbon microbead, coke derived from petroleum or coal tar pitch, soft carbon, hard carbon, etc.

[0207] The alloy of lithium metal may be an alloy of lithium and a metal selected from the following: Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.

[0208] The material capable of doping and dedoping lithium may be Si, Si-C composite material, SiOx (0 < x < 2), Si-Q alloy (where Q is an element selected from the following: alkali metal, alkaline earth metal, Group 13 element, Group 14 element, Group 15 element, Group 16 element, transition metal, rare earth element, and combinations thereof; but not including Si), Sn, SnO 2 、Sn-R alloy (where R is an element selected from the following: alkali metal, alkaline earth metal, Group 13 element, Group 14 element, Group 15 element, Group 16 element, transition metal, rare earth element, and combinations thereof; but not including Sn), etc. In addition, the material capable of doping and dedoping lithium used herein may include a mixture of SiO 2 and at least one of the above examples. Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.

[0209] In addition, the transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanium oxide, etc.

[0210] Preferably, the negative electrode may include at least one negative electrode active material selected from the following: carbonaceous materials and silicon compounds.

[0211] Herein, the carbonaceous material may be at least one material selected from the following: natural graphite, artificial graphite, condensate graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, mesophase carbon microbeads, coke derived from petroleum or coal tar pitch, soft carbon, and hard carbon, as exemplified above. And the silicon compound may be a compound containing Si as exemplified above, i.e., Si, Si-C composite material, SiOx (0 < x < 2), Si-Q alloy, a mixture thereof, or SiO 2 And a mixture with at least one of them.

[0212] According to one embodiment, based on the total weight of the negative electrode material, the content of the negative electrode active material may be 85 wt% to 98 wt%.

[0213] Specifically, based on the total weight of the negative electrode material, the content of the negative electrode active material may be 85 wt% or more, 87 wt% or more, or 90 wt% or more; and 98 wt% or less, 97 wt% or less, or 95 wt% or less.

[0214] Preferably, based on the total weight of the negative electrode material, the content of the negative electrode active material may be 85 wt% to 97 wt%, 87 wt% to 97 wt%, 87 wt% to 95 wt%, or 90 wt% to 95 wt%.

[0215] Regarding the content of the conductive material, binder, and current collector included in the negative electrode material, refer to the description provided in the above "IV. Positive Electrode for Lithium Secondary Battery".

[0216] The separator separates the positive electrode and the negative electrode and provides a channel for the movement of lithium ions. As the separator, any separator known to be applicable to lithium secondary batteries in the field to which the present invention pertains can be used without any particular limitation. Preferably, the separator has excellent wettability to the electrolyte and low resistance to ion migration of the electrolyte.

[0217] Specifically, the separator may be a porous polymer film made of polyolefin polymers such as polyethylene, polypropylene, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-methyl acrylate copolymer, etc. The separator may be a multilayer film in which the porous polymer film is laminated into two or more layers. The separator may be a non-woven fabric containing glass fiber, polyethylene terephthalate fiber, etc. Additionally, the separator may be coated with a ceramic component or a polymer material to ensure heat resistance or mechanical strength.

[0218] As electrolyte, electrolytes known to be applicable to lithium secondary batteries in the field of the present invention can be used without any particular restrictions. For example, the electrolyte can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.

[0219] Specifically, the electrolyte may include a nonaqueous organic solvent and a lithium salt.

[0220] The nonaqueous organic solvent may be used without any particular limitation as long as it can serve as a medium through which ions participating in the electrochemical reaction of the battery can move.

[0221] Specifically, the non-aqueous organic solvent may include: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents ethanol and isopropanol; nitriles such as R-CN (R is a C2 to C20 linear, branched or cyclic hydrocarbon group, which may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; cyclopentane sulfone, etc.

[0222] Among the above examples, a carbonate-based solvent may be preferably used as the nonaqueous organic solvent.

[0223] In particular, considering the charge / discharge performance of the battery and the compatibility with the sacrificial positive electrode material, the non-aqueous organic solvent used herein may preferably be a mixture of a cyclic carbonate (e.g., ethylene carbonate and propylene carbonate) with high ion conductivity and high dielectric constant and a linear carbonate (e.g., ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate) with low viscosity. When the cyclic carbonate and the linear carbonate are mixed and used in a volume ratio of 1:1 to 1:9, it may be beneficial to exhibit the above-mentioned properties.

[0224] In addition, the non-aqueous organic solvent used herein may preferably include: a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1-3:1-9:1.

[0225] The lithium salt contained in the electrolyte may be dissolved in the nonaqueous organic solvent to serve as a supply source of lithium ions in the battery, thereby enabling the basic operation of the lithium secondary battery and playing a role in facilitating the movement of lithium ions between the positive electrode and the negative electrode.

[0226] Specifically, the lithium salt may include LiPF 6、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 、LiN(SO 2 F) 2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiCl, LiI, LiB(C 2 O 4 ) 2 Preferably, the lithium salt may be LiPF 6 , LiFSI or a mixture thereof.

[0227] The lithium salt may be included in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt included in the concentration range may impart appropriate conductivity and viscosity to the electrolyte, thereby achieving excellent electrolyte performance.

[0228] Optionally, the electrolyte may contain additives in order to improve battery life, suppress reduction in battery capacity, and improve battery discharge capacity.

[0229] For example, the additives may include: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, glycol dimethyl ethers, hexamethylphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. The additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0230] Beneficial Effects

[0231] The lithium transition metal oxide according to the present invention can maintain a stable lattice structure when introducing hetero elements therein, thereby minimizing side reactions with electrolytes, thereby inhibiting gas generation during charging and discharging of lithium secondary batteries. The positive electrode additive for lithium secondary batteries containing lithium transition metal oxides can make it possible to improve the safety and life of lithium secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0232] Figure 1 : is a graph showing the relationship between the irreversible capacity and the gas generation amount of the lithium secondary batteries of Examples 1 to 5 and Comparative Examples 1 to 2.

[0233] Figure 2 : is a graph showing the relationship between the irreversible capacity of the lithium secondary batteries of Examples 6 to 12 and the amount of gas generated.

[0234] Figure 3 is a graph showing changes in the capacity retention ratio of the lithium secondary batteries of Example 13 and Comparative Examples 3 to 6 with accumulated charge / discharge cycles. DETAILED DESCRIPTION

[0235] Hereinafter, the functions and effects of the present invention will be described in more detail by specific examples. However, these examples are provided for exemplary purposes only. The scope of the present invention is not limited by these examples, and it is obvious to those skilled in the art that various changes and variants can be accomplished within the scope and spirit of the present invention.

[0236] Example 1

[0237] (1) Synthesis of lithium transition metal oxides

[0238] By 2 O, CoO, ZnO, and MgO were solid-phase mixed at a molar ratio of Li:Co:Zn:Mg=6:0.77:0.2:0.03 to prepare a raw material mixture.

[0239] The raw material mixture was heated at a heating rate of 1.6°C / min for 6 hours under an Ar atmosphere and then calcined at 600°C for 12 hours to obtain Li 6 Co 0.77 Zn 0.2 Mg 0.03 O 4 of lithium transition metal oxides.

[0240] The lithium transition metal oxide is crushed using a jaw crusher and then classified using a vibrating screen.

[0241] The lithium transition metal oxide and distilled water were mixed at a weight ratio of 1:2 and stirred to wash the lithium transition metal oxide. The washed lithium transition metal oxide was dried by heat treatment at 180° C. for 1 hour.

[0242] (2) Preparation of lithium secondary batteries

[0243] By using lithium transition metal oxide (Li 6 Co 0.77 Zn 0.2 Mg 0.03 O 4 ), carbon black as a conductive material and polyvinylidene fluoride (PVdF) as a binder were mixed in an organic solvent (N-methylpyrrolidone) at a weight ratio of 95:3:2 to prepare a positive electrode material slurry. The positive electrode material slurry was coated on one surface of a current collector, and rolled and dried to prepare a positive electrode, and the current collector was an aluminum foil with a thickness of 15 μm. For reference, in this experiment, no positive electrode active material was added to the positive electrode material. The addition of the positive electrode active material is shown in Example 13 below.

[0244] A negative electrode material slurry was prepared by mixing natural graphite as a negative electrode active material, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a binder in an organic solvent (N-methylpyrrolidone) at a weight ratio of 95:3:2. The negative electrode material slurry was coated on one surface of a current collector, which was a copper foil with a thickness of 15 μm, and rolled and dried to prepare a negative electrode.

[0245] The non-aqueous organic solvent was prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:4:3. 6 The electrolyte was prepared by dissolving a lithium salt of LiFSI with a concentration of 0.5 M in a non-aqueous organic solvent.

[0246] The electrode assembly is prepared by inserting porous polyethylene as a separator between the positive electrode and the negative electrode, and the electrode assembly is placed in a case. The lithium secondary battery in the form of a pouch cell is manufactured by injecting an electrolyte into the case.

[0247] Example 2

[0248] In addition to using Al 2 O 3 In addition to replacing MgO, (1) lithium transition metal oxide Li 6 Co 0.77 Zn 0.2 Al 0.03 O4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0249] Example 3

[0250] In addition to using TiO 2 In addition to replacing MgO, (1) lithium transition metal oxide Li 6 Co 0.77 Zn 0.2 Ti 0.03 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0251] Example 4

[0252] In addition to using ZrO 2 In addition to replacing MgO, (1) lithium transition metal oxide Li 6 Co 0.77 Zn 0.2 Zr 0.03 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0253] Example 5

[0254] In addition to using Nb 2 O 5 In addition to replacing MgO, (1) lithium transition metal oxide Li 6 Co 0.77 Zn 0.2 Nb 0.03 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0255] Example 6

[0256] In addition to using the 2 O, CoO, ZnO and Al 2 O 3 In addition to the raw material mixture obtained by solid phase mixing at a molar ratio of Li:Co:Zn:Al=6:0.7:0.25:0.05, (1) lithium transition metal oxide Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0257] Example 7

[0258] In addition to using MgO instead of Al 2 O 3 In addition, (1) lithium transition metal oxide Li 6 Co 0.7 Zn 0.25 Mg 0.05 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0259] Example 8

[0260] In addition to using the 2 O, CoO, ZnO and TiO 2 In addition to the raw material mixture obtained by solid phase mixing at a molar ratio of Li:Co:Zn:Ti=6:0.72:0.25:0.03, (1) lithium transition metal oxide Li 6 Co 0.72 Zn 0.25 Ti 0.03 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0261] Example 9

[0262] In addition to using ZrO 2 Replace TiO 2 In addition, (1) lithium transition metal oxide Li 6 Co 0.72 Zn 0.25 Zr 0.03 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0263] Example 10

[0264] In addition to using the 2 O, CoO, ZnO and Al 2 O 3 In addition to the raw material mixture obtained by solid phase mixing at a molar ratio of Li:Co:Zn:Al=6:0.65:0.3:0.05, (1) lithium transition metal oxide Li 6 Co 0.65 Zn 0.3 Al0.05 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0265] Embodiment 11

[0266] In addition to using the 2 O, CoO, ZnO and Al 2 O 3 In addition to the raw material mixture obtained by solid phase mixing at a molar ratio of Li:Co:Zn:Al=6:0.65:0.25:0.1, (1) lithium transition metal oxide Li 6 Co 0.65 Zn 0.25 Al 0.1 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0267] Example 12

[0268] In addition to using the 2 O, CoO, ZnO and Al 2 O 3 In addition to the raw material mixture obtained by solid phase mixing at a molar ratio of Li:Co:Zn:Al=6:0.6:0.3:0.1, (1) lithium transition metal oxide Li 6 Co 0.6 Zn 0.3 Al 0.1 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0269] Embodiment 13

[0270] A lithium secondary battery was manufactured by the same method as in Example 6 above, except that a positive electrode active material was further added in the preparation of the positive electrode and the composition of the negative electrode active material was changed in the preparation of the negative electrode.

[0271] Specifically, NCMA (Li[Ni, Co, Mn, Al]O 2 ) compounds (NTA-X12M, L&F), lithium transition metal oxides (Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4), carbon black as a conductive material and polyvinylidene fluoride (PVdF) as a binder were mixed in an organic solvent (N-methylpyrrolidone) at a weight ratio of 93.8:1.2:3:2 to prepare a positive electrode material slurry. The positive electrode material slurry was coated on one surface of a current collector, and rolled and dried to prepare a positive electrode, and the current collector was an aluminum foil with a thickness of 15 μm.

[0272] A negative electrode material slurry was prepared by mixing a mixture of natural graphite and SiO (weight ratio = 9:1) as a negative electrode active material, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a binder in an organic solvent (N-methylpyrrolidone) at a weight ratio of 95:3:2. The negative electrode material slurry was coated on one surface of a current collector, which was a copper foil with a thickness of 15 μm, and rolled and dried to prepare a negative electrode.

[0273] The electrode assembly is prepared by inserting porous polyethylene as a separator between the positive electrode and the negative electrode, and the electrode assembly is placed in a case. The lithium secondary battery in the form of a pouch cell is manufactured by injecting an electrolyte into the case.

[0274] Comparative Example 1

[0275] In addition to mixing Li with a molar ratio of Li:Co=6:1 without adding ZnO and MgO, 2 O and CoO were used to prepare (1) a lithium transition metal oxide Li 6 CoO 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0276] Comparative Example 2

[0277] In addition to mixing Li with a molar ratio of Li:Co:Zn=6:0.7:0.3 without adding MgO 2 O, CoO and ZnO were used to prepare (1) a lithium transition metal oxide Li 6 Co 0.7 Zn 0.3 O 4 and (2) a lithium secondary battery comprising the same as a positive electrode additive.

[0278] Comparative Example 3

[0279] In addition to using the Li obtained in Comparative Example 1 in the preparation of the positive electrode 6 CoO 4 Replace Li 6 Co 0.7 Zn0.25 Al 0.05 O 4 A lithium secondary battery was manufactured by the same method as in Example 13 except for using the positive electrode additive.

[0280] Comparative Example 4

[0281] In addition to using the Li obtained in Comparative Example 2 in the preparation of the positive electrode 6 Co 0.7 Zn 0.3 O 4 Replace Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4 A lithium secondary battery was manufactured by the same method as in Example 13 except for using the positive electrode additive.

[0282] Comparative Example 5

[0283] In addition to the NCMA (Li[Ni,Co,Mn,Al]O as the positive electrode active material in a weight ratio of 91.2:3.8:3:2 in the preparation of the positive electrode, 2 ) compounds (NTA-X12M, L&F), as cathode additives to replace lithium transition metal oxides (Li 6 Co 0.7 Zn 0.25 Al 0.05 O 4 ) of DN2O(Li 2 NiO 2 A lithium secondary battery was manufactured by the same method as in Example 13, except that carbon black as a conductive material and polyvinylidene fluoride (PVdF) as a binder were mixed.

[0284] Comparative Example 6

[0285] A lithium secondary battery was manufactured by the same method as in Example 13, except that no positive electrode additive was added during the preparation of the positive electrode.

[0286] Test Example 1

[0287] The particle size distribution of the lithium transition metal oxides obtained in Examples 1 to 12 and Comparative Examples 1 and 2 was measured using a laser diffraction scattering particle size distribution analyzer (product name: Partica LA-960V2, manufacturer: HORIBA). At this time, N-methylpyrrolidone (NMP) was used as a dispersion medium for the lithium transition metal oxide for measurement.

[0288] [Table 1]

[0289]

[0290] Referring to Table 1, it was confirmed that the lithium transition metal oxides of the examples simultaneously satisfied the D50 value of 10.0 μm to 25.0 μm and the D max / D min value.

[0291] Referring to Comparative Examples 1 and 2, as Zn is introduced into Li 6 CoO 4 The D50 value of the particles tends to increase.

[0292] In addition, the particle size distribution changes with the additionally introduced element. In particular, when Al is further introduced into the lithium transition metal oxide into which Zn is introduced, D min The value tends to increase and D max For example, it was confirmed that the D values ​​of Examples 2, 6, 10, 11, and 12 in which Al was introduced max / D min less than 30, which is less than D of Examples 1, 3, 4, 5, 7 and 9 in which Mg, Ti, Zr or Nb is introduced. max / D min The D of Example 8 in which Ti was introduced max / D min The value is less than 30, but it has a larger D max value (87.7μm).

[0293] Test Example 2

[0294] For the lithium secondary batteries obtained in the above Examples 1 to 12 and the above Comparative Examples 1 and 2, the cumulative gas generation amount was measured with the cumulative charge / discharge cycle by the following method, and the measured gas generation amount with the cumulative charge capacity is shown in Table 2. Figure 1 and Figure 2 The changes in the cumulative gas generation during high temperature storage are shown in Table 3.

[0295] (1) Measurement of formation (initial charge) capacity and charge / discharge capacity

[0296] The pouch cell type lithium secondary battery was cycled at 45° C. and 0.1 C with constant current-constant voltage charging to 4.25 V and constant current discharging to 2.5 V with a 20 minute rest between charging and discharging, and then the formation capacity and charge / discharge capacity were measured.

[0297] (2) Measurement of cumulative gas generation as a function of charge / discharge

[0298] After the lithium secondary battery was operated under the charge / discharge conditions of (1) above, the pouch battery was temporarily recovered in a discharged state when measuring the gas generation amount. Using a densimeter (MATSUHAKU, TWD-150DM), the difference between the original weight of the pouch battery and its weight in water was measured to calculate the volume change of the pouch battery, and the volume change was divided by the weight of the electrode active material to calculate the gas generation amount per unit weight.

[0299] (3) Measurement of cumulative gas generation as a function of high-temperature storage

[0300] The pouch cell type lithium secondary battery was subjected to constant current-constant voltage charging at a temperature of 45° C. and 0.1C to 4.25 V, collected to measure the formation capacity, and then stored in a chamber at 60° C. The lithium secondary battery was taken out every other week to measure the difference between the original weight of the pouch cell and its weight in water using a densimeter (MATSUHAKU, TWD-150DM) and calculate the volume change of the pouch cell, after which the volume change was divided by the weight of the electrode active material to calculate the gas generation per unit weight.

[0301] Table 2 below shows the cumulative gas generation after the 1st, 2nd, 10th, 30th and 50th cumulative cycles after formation (0th charge / discharge).

[0302] [Table 2]

[0303]

[0304] As shown in Table 2 and Figure 1 As shown, the initial charge capacity of Examples 1 to 5 is smaller than that of Comparative Examples 1 and 2. However, the cumulative gas generation after the 50th cycle in Examples 1 to 5 is 1 mL / g or less, which shows a very excellent effect of reducing gas. In particular, Example 1 has the largest initial charge capacity among the examples, and also has a relatively small cumulative gas generation. In Example 2, although the initial charge capacity is somewhat low, the cumulative gas generation is the lowest, indicating an excellent effect of reducing gas.

[0305] As shown in Table 2 and Figure 2 As shown, in the case of Ti and Zr, the additional effect of reducing gas by adding the impurity element is relatively insignificant. Referring to Examples 6, 10, 11 and 12, it was confirmed that the higher the molar content of Al, the greater the effect of reducing gas.

[0306] Table 3 below shows the cumulative gas generation after formation (0th charge) and storage at 60° C. for 1, 2, 3 and 4 weeks.

[0307] [Table 3]

[0308]

[0309] As shown in Table 3, it was confirmed that Examples 1 to 5 had a significantly superior gas reduction effect compared to Comparative Examples 1 and 2, in which the cumulative gas generation amount in high-temperature storage at 60° C. was 1 mL / g or less.

[0310] Referring to Examples 6 to 12, it was confirmed that the lithium transition metal oxide into which Al was introduced had an excellent effect of reducing gas during high-temperature storage.

[0311] Test Example 3

[0312] For the lithium secondary batteries of Example 13 and Comparative Examples 3 to 6 in which the positive electrode active material and the positive electrode additive were mixed and applied, the capacity retention rate and the cumulative gas generation amount were measured with the cumulative charge / discharge cycles by the following method, and the measured capacity retention rate and the cumulative gas generation amount are shown in Figure 3 Figure and Table 4.

[0313] (1) Measurement of formation (initial charge) capacity and charge / discharge capacity

[0314] The pouch cell type lithium secondary battery was cycled with constant current-constant voltage charge to 4.25 V and constant current discharge to 2.5 V at 45° C. and 0.1 C with 20 minutes of rest between charge and discharge, and then the formation capacity and the charge / discharge capacity up to the 100th cycle were measured.

[0315] (2) Measurement of cumulative gas generation as a function of cumulative charge / discharge

[0316] After the lithium secondary battery was operated under the charge / discharge conditions of (1) above, the pouch battery was temporarily recovered in a discharged state when measuring the gas generation amount. Using a densimeter (MATSUHAKU, TWD-150DM), the difference between the original weight of the pouch battery and its weight in water was measured to calculate the volume change of the pouch battery, and the volume change was divided by the weight of the electrode active material to calculate the gas generation amount per unit weight.

[0317] (3) Measurement of cumulative gas generation as a function of high-temperature storage

[0318] The pouch cell type lithium secondary battery was subjected to constant current-constant voltage charging at a temperature of 45° C. and 0.1C to 4.25 V, collected to measure the formation capacity, and then stored in a chamber at 60° C. The lithium secondary battery was taken out every other week to measure the difference between the original weight of the pouch cell and its weight in water using a densimeter (MATSUHAKU, TWD-150DM) and calculate the volume change of the pouch cell, after which the volume change was divided by the weight of the electrode active material to calculate the gas generation per unit weight.

[0319] Table 4 below shows the formation (0th charge / discharge) capacity, the cumulative gas generation after the 50th and 100th cumulative cycles, and the discharge capacity retention ratio after the 100th cycle.

[0320] [Table 4]

[0321]

[0322] As shown in Table 4 above and Figure 3 As shown in , the discharge capacity of Example 13 and Comparative Examples 3 to 5 is greater than that of Comparative Example 6 in which the positive electrode additive (positive electrode sacrificial material) is not applied. It can be seen that the sacrificial positive electrode material compensates for the irreversible lithium consumed when the SEI layer is formed at the negative electrode.

[0323] In contrast, in the case of Comparative Example 6, the positive electrode material was not sacrificed to compensate for the irreversible lithium, and thus the lithium in the positive electrode material was consumed, resulting in a decrease in the discharge capacity and the discharge capacity was 201.3 mAh / g.

[0324] In the case of Example 13, the cumulative gas generation amount at the 100th cycle was 0.07 mL / g, which was lower than 0.24 mL / g of Comparative Example 3 and lower than 0.16 mL / g of Comparative Example 4. In Example 13, since the Li 6 Co 0.7 Zn 0.3 O 4 Since Al is further introduced into the Zn, the CoO generated after the initial charge is more effectively stabilized compared with the case where only Zn is introduced. 2 Therefore, the side reaction with the electrolyte is effectively prevented, thereby suppressing additional gas generation.

[0325] In the case of Comparative Example 5, the cumulative gas generation amount at the 50th cycle was the smallest, which was 0.02 mL / g, but the increase in gas generation from the 50th cycle to the 100th cycle was 0.09 mL / g, so there is a chance that gas generation will continue to increase thereafter. This is also the same as Comparative Example 3. In contrast, in the case of Example 13, the increase in gas generation from the 50th cycle to the 100th cycle was 0.02 mL / g, from which it can be seen that gas generation is suppressed as the charge / discharge cycle continues.

[0326] In the case of Example 13, Comparative Example 3, and Comparative Example 4, in which a Co-based sacrificial positive electrode material is applied, the capacity retention rate at the 100th cycle is 88.2% or more. The capacity retention rates of Comparative Example 5, in which a Ni-based sacrificial positive electrode material is applied, and Comparative Example 6, in which a sacrificial positive electrode material is not applied, are 86.3% and 86.2%, respectively, which are significantly lower than that of Example 13. In particular, in the case of Example 13 in which Al is further introduced, it is confirmed that the capacity retention rate is significantly improved to 91.7%. This may be because the addition of Al stabilizes the crystal phase after the initial charge to prevent side reactions with the electrolyte, as seen in the cumulative gas generation described above.

[0327] Therefore, when a Co-based sacrificial positive electrode material, particularly a sacrificial positive electrode material having a composition of Chemical Formula 1, is applied to a lithium secondary battery containing an actual positive electrode material, it can be confirmed that the material retains the initial discharge capacity and suppresses the amount of gas generated within the battery, and is also excellent in capacity retention after 100 cycles.

[0328] Table 5 below shows the cumulative gas generation after formation (0th charge) and storage at 60° C. for 1, 2, 3 and 4 weeks.

[0329] [Table 5]

[0330]

[0331] As shown in Table 5 above, Example 13 had the lowest cumulative gas generation after 4 weeks, which was 0.15 mL / g. This may be because, as in the results of the charge / discharge cycle, the introduction of Li 6 CoO 4 The heteroelement in the 2 , thereby preventing a side reaction with the electrolyte, thereby suppressing additional gas generation.

[0332] In addition, Example 13 generates less gas than Comparative Example 6 which does not apply a sacrificial positive electrode material, and this result may be an experimental error, or the positive electrode additive contained in the lithium secondary battery tends to not only suppress gas generation but also absorb the generated gas.

[0333] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is apparent to those skilled in the art that various modifications and variations are possible within the technical concept of the present invention and within the equivalent scope of the claims.

Claims

1. A lithium transition metal oxide, wherein the lithium transition metal oxide is a lithium cobalt oxide containing a heteroelement, wherein the heteroelement comprises: a 4th period transition metal; and at least one element selected from a 2nd group element, a 13th group element, a 14th group element, a 5th period transition metal, and a 6th period transition metal, and When the particle size distribution is measured by laser diffraction scattering, the cumulative 50% particle size D50 is 10.0 μm to 25.0 μm, and the maximum particle size D max With the minimum particle size D min Ratio D max / D min 10.0 to 60.0, The lithium transition metal oxide is represented by the following chemical formula 1: [Chemical formula 1] Li6Co 1-x-y Zn x M y O4 In Chemical Formula 1, M is at least one element selected from Al, Mg, Ti, Zr and Nb, x is 0.1 to 0.7, y is 0.01 to 0.

2.

2. The lithium transition metal oxide according to claim 1, The lithium transition metal oxide has a cumulative 5% particle size D5 of 3.0 μm to 10.0 μm and a cumulative 95% particle size D95 of 20.0 μm to 45.0 μm when measured by laser diffraction scattering particle size distribution.

3. The lithium transition metal oxide according to claim 1, The lithium transition metal oxide comprises at least one selected from the following: Li6Co 0.77 Zn 0.2 Al 0.03 O4、Li6Co 0.76 Zn 0.2 Al 0.04 O4、Li6Co 0.75 Zn 0.2 Al 0.05 O4、Li6Co 0.7 Zn 0.25 Al 0.05 O4、Li6Co 0.65 Zn 0.25 Al 0.1 O4、Li6Co 0.67 Zn 0.3 Al 0.03 O4、Li6Co 0.66 Zn 0.3 Al 0.04 O4、Li6Co 0.65 Zn 0.3 Al 0.05 O4、Li6Co 0.6 Zn 0.3 Al 0.1 O4、Li6Co 0.77 Zn 0.2 Mg 0.03 O4、Li6Co 0.76 Zn 0.2 Mg 0.04 O4、Li6Co 0.75 Zn 0.2 Mg 0.05 O4、Li6Co 0.7 Zn 0.25 Mg 0.05 O4、Li6Co 0.67 Zn 0.3 Mg 0.03 O4、Li6Co 0.66 Zn 0.3 Mg 0.04 O4、Li6Co 0.65 Zn 0.3 Mg 0.05 O4、Li6Co 0.77 Zn 0.2 Ti 0.03 O4、Li6Co 0.76 Zn 0.2 Ti 0.04 O4、Li6Co 0.75 Zn 0.2 Ti 0.05 O4、Li6Co 0.72 Zn 0.25 Ti 0.03 O4, Li6Co 0.67 Zn 0.3 Ti 0.03 O4, Li6Co 0.66 Zn 0.3 Ti 0.04 O4, Li6Co 0.65 Zn 0.3 Ti 0.05 O4, Li6Co 0.77 Zn 0.2 Zr 0.03 O4, Li6Co 0.76 Zn 0.2 Zr 0.04 O4, Li6Co 0.75 Zn 0.2 Zr 0.05 O4, Li6Co 0.72 Zn 0.25 Zr 0.03 O4, Li6Co 0.67 Zn 0.3 Zr 0.03 O4, Li6Co 0.66 Zn 0.3 Zr 0.04 O4, Li6Co 0.65 Zn 0.3 Zr 0.05 O4, Li6Co 0.77 Zn 0.2 Nb 0.03 O4, Li6Co 0.76 Zn 0.2 Nb 0.04 O4, Li6Co 0.75 Zn 0.2 Nb 0.05 O4, Li6Co 0.67 Zn 0.3 Nb 0.03 O4, Li6Co 0.66 Zn 0.3 Nb 0.04 O4 and Li6Co 0.65 Zn 0.3 Nb 0.05 O4.

4. A method for preparing a lithium transition metal oxide, the method comprising: The first step: solid phase mixing of lithium oxide, cobalt oxide and heteroelement oxide; as well as The second step: obtaining the lithium transition metal oxide according to claim 1 by calcining the mixture obtained in the first step at a temperature of 550° C. to 750° C. under an inert atmosphere.

5. The method for preparing a lithium transition metal oxide according to claim 4, In the second step, the mixture obtained in the first step is heated at a heating rate of 1.4° C. / min to 2.0° C. / min under an inert atmosphere to be calcined at a temperature of 550° C. to 750° C. for 2 to 20 hours. 6 . A positive electrode additive for a lithium secondary battery, comprising the lithium transition metal oxide according to claim 1 . 7 . A positive electrode for a lithium secondary battery, comprising: a positive electrode active material, a binder, a conductive material and the lithium transition metal oxide according to claim 1 . 8 . A positive electrode for a lithium secondary battery, comprising: a positive electrode active material, a binder, a conductive material and the positive electrode additive for a lithium secondary battery according to claim 6 . 9 . A lithium secondary battery, comprising: the positive electrode for a lithium secondary battery according to claim 7 or 8 ; a negative electrode; a separator; and an electrolyte.

10. The lithium secondary battery according to claim 9, The negative electrode includes at least one negative electrode active material selected from the group consisting of a carbonaceous material and a silicon compound.

Citation Information

Patent Citations

  • Positive active material for rechargeable lithium battery and rechargeable lithium battery including same

    KR1020130079109A

  • Positive electrode additive material for rechargeable lithium battery, method of preparing the same, positive electrode including the same and rechargeable lithium battery including the same

    KR1020200066048A

  • Infusion pump with tube loading guidance and confirmation function

    KR1020210009337A

  • Display device

    KR1020210106774A

  • Wearable large robot

    KR1020210106775A